Economic development and the blue economy: insights from the NEXT 11 countries - Imran, Muhammad (2025)
Purpose This study aims to investigate the influence of the blue economy on the economic growth of the NEXT 11 countries − Bangladesh, Egypt, Indonesia, Iran, Mexico, Nigeria, Pakistan, the Philippines, Turkey, South Korea and Vietnam − from 1995 to 2018. Design/methodology/approach The Solow model serves as the study’s theoretical framework, while econometric approaches such as panel-corrected standard errors (PCSE) and system-GMM are used to account for potential endogeneity and cross-sectional dependence. The important factors studied are gross domestic product, total fisheries output, value added from agriculture, forestry, and fishing, aquaculture production, labour, capital, interest rates, inflation rates and trade. A rigorous statistical analysis has been performed for estimation. Findings The findings show that fisheries and aquaculture provide a considerable contribution to economic growth, which has important implications for sustainability. Practical implications The findings underscore the necessity of enhancing fisheries management and promoting regional collaboration within the blue economy to maximize economic advantages and ensure sustainable growth in these nations. Originality/value This report highlights the essential significance of the blue economy in fostering economic progress, providing an in-depth analysis of its importance to the NEXT 11 nations over a prolonged period.